2010
DOI: 10.1371/journal.pbio.1000460
|View full text |Cite
|
Sign up to set email alerts
|

Prox1 Is Required for Granule Cell Maturation and Intermediate Progenitor Maintenance During Brain Neurogenesis

Abstract: The transcription factor Prox1 plays a crucial role in intermediate progenitor maintenance and hippocampal neuron differentiation during adult neurogenesis in the dentate gyrus region of the hippocampus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
203
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(214 citation statements)
references
References 57 publications
5
203
0
6
Order By: Relevance
“…Taken together, our data suggest that Prox1 is (i) required for proper neuronal differentiation of granule cells, (ii) sufficient to enhance neuronal differentiation of newborn cells in the adult DG, and (iii) not required for granule cell survival after they have fully matured. Thus, our findings confirm and extend the results recently obtained by using a transgenesis-based approach (17).…”
Section: Prox1 Has a Stage-specific Role In The Course Of Adult Hipposupporting
confidence: 92%
See 3 more Smart Citations
“…Taken together, our data suggest that Prox1 is (i) required for proper neuronal differentiation of granule cells, (ii) sufficient to enhance neuronal differentiation of newborn cells in the adult DG, and (iii) not required for granule cell survival after they have fully matured. Thus, our findings confirm and extend the results recently obtained by using a transgenesis-based approach (17).…”
Section: Prox1 Has a Stage-specific Role In The Course Of Adult Hipposupporting
confidence: 92%
“…Prox1 is a prospero-related homeodomain transcription factor, which is highly expressed in DG granule cells (10,15,16). Prox1 has previously been shown to be important for lens development, lymphangiogenesis, differentiation of certain spinal cord interneurons, and, very recently, in hippocampal granule cell genesis (17)(18)(19)(20). We analyzed the murine Prox1 promoter/enhancer regions for TCF/LEF sites and found two TCF/LEF consensus sites 49 kb and 43 kb upstream of the Prox1 start codon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted, however, that a decrease in cell death may simply be a reflection of the fact that there are reduced numbers of new-born neurons present in the mutant hippocampus. Finally, the qPCR analysis also confirmed that the expression of Tnc, Fabp7, Hes5 and the dentate granule neuron marker prospero homeobox protein-1 (Prox1) 24 was significantly reduced in the mutant in comparison to the controls (Fig. 1C).…”
mentioning
confidence: 57%